THE REFORM OF DISPUTE SETTLEMENT SYSTEM OF THE WORLD TRADE ORGANIZATION: CONTRIBUTION AND PERSPECTIVES FROM INDONESIA - Handian Putra, Angga (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2024)
The WTO dispute settlement system is currently in crisis as the Appellate Body has been unable to perform its appellate review since December 11th, 2019. The US asserted that the AB has exceeded its authority. The crisis can be detrimental, especially for developing countries in international trade. The WTO Members have made efforts to reform the system. This paper uses qualitative and descriptive research to analyse the contribution of Indonesia to the system and its perspectives on the reform negotiations. Indonesia has contributed to the system and the Organization by clarifying interpretations of WTO agreements. In the reform negotiations, Indonesia has actively participated by joining a proposal to commence the selection of new AB members, supporting the result of “Walker Process” negotiations as a basis for future negotiation, and making some proposals such as formal communication to the WTO on a process in an informal process to implement the mandate of MC12 Outcome Document. As a negotiation strategy, Indonesia should continue its active participation by prioritizing accessible aspects that are interests of developing and LDC members, emphasizing the need to limit negotiation scope and urging the fulfilment of the 2024 deadline, safeguarding a legalistic system, and conducting a comprehensive analysis on two-tier litigation.